Myths about Islamic educational institutions: the case of IIUM - Hasan, Md. Mahmudul (2020)
Many people associate Islamic educational Institutions, including International Islamic University Malaysia (IIUM), with backwardness, rigidity and anti-modernity. Located in Kuala Lumpur, IIUM was established in 1983 to integrate Islam into mainstream education. It offers almost all subjects taught in conventional universities. However, mainly because of the term ‘Islamic’ in its name, some believe that it produces only imams and religious teachers to staff masjids and madrasas. Since its inception, IIUM has been helping many students know themselves and gather confidence. It gives them a sense of pride and helps them hone their abilities and reconnect with the divine in full harmony with their fitrah (the natural, original state in which God created humans). It is committed to producing ethically-grounded future leaders who will unleash their potential for self and others.